THE THIRD MISSION OF THE ARMED FORCES OF THE REPUBLIC OF BULGARIA: THE THIRD MISSION OF THE ARMED FORCES OF THE REPUBLIC OF BULGARIA - Antonova, Mariela; Antonov, Stamen (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
This article examines the concept, legal framework, and practical implementation of the Third Mission of the Armed Forces of the Republic of Bulgaria — their participation in assisting the civilian population in crisis situations, disasters, and emergencies. It discusses the transformation of the Bulgarian Armed Forces after the end of the Cold War, their integration into NATO and the EU, and the role of civil-military cooperation in national and regional security. The study highlights examples of the Third Mission’s application, such as disaster relief, humanitarian aid, and pandemic response, while outlining the challenges related to resources, training, and coordination with civilian institutions.